EVE 3 BIBOTE Soft Candies: A Functional Food Intervention for Anemia in Adolescent Girls - Fiky Trisna Nilasari; Yanti Herawati; Herri S. Sastramidardja (Jurnal Ilmu Multidisiplin, 2025)
Anemia remained a significant public health issue among adolescent girls due to increased iron requirements and inadequate dietary intake. This study aimed to evaluate the effect of a functional food innovation, a soft candy formulated from beetroot, carrot, and broccoli (Eve 3 Bibote), on improving hemoglobin levels among anemic adolescent girls. The research was conducted at SMKN 1 Gunung Putri, Bogor Regency, in 2025 using an experimental design with pre- and post-intervention measurements. Participants were adolescent girls diagnosed with anemia who consumed the soft candy for a specified intervention period. Hemoglobin levels were measured before and after the intervention to assess the effect. The findings showed a significant increase in hemoglobin levels after the administration of the soft candy, indicating its potential as a complementary approach for anemia management. This study concluded that the functional combination of beetroot, carrot, and broccoli in soft candy form was effective in supporting hemoglobin improvement among adolescent girls with anemia. The results highlighted the potential application of plant-based functional foods in school-based nutrition programs to reduce anemia prevalence in adolescents.